Phyllosphere of senescent crops as a microbial N2O source - Tago, Kanako; Tokuda, Shin-Ichi; Sato, Yuya; Sekiyama, Yasuyo; Guo, Yong; Wang, Yong; Date, Yasuhiro; Hara, Shintaro; Kuroiwa, Megumi; Ohbayashi, Tsubasa; Aoyagi, Luciano Nobuhiro; Nishizawa, Tomoyasu; et al. (Frontiers in Microbiology, 2026)
Plant residues contribute to the nitrogen cycle in terrestrial ecosystems, as they are recognized as a nutrient source for soil microorganisms. However, the contribution of the microbial community in the phyllosphere of plant residues, such as senescent leaves, itself in the nitrogen cycle remains unclear. In agricultural lands, crop residues contribute to global emissions of the greenhouse gas nitrous oxide (N2O), which is an intermediate product of several microbial pathways including nitrification and denitrification. We examined direct N2O emissions from aboveground cabbage leaf residues via denitrification by indigenous microbial communities inhabiting the phyllosphere of the residue. We conducted a variety of experiments, ranging from field experiments to multi-omics analyses. We found that cabbage leaves accumulated nitrate from 3.0 to 11.3 NO3–-N mg g–1 leaf dry weight by application of chemical fertilizers and/or cow manure compost. Leaf senescence triggered N2O emissions (8.62–415.35 μg N2O–N m–2 h–1), and denitrifiers from five genera were isolated from the senescent leaves. A representative denitrifier, Agrobacterium sp. 6Ca8 utilized leaf nitrate as an electron acceptor and carbon sources such as glucose, succinate, and pyroglutamate as electron donors to produce N2O. Strain 6Ca8 co-expressed genes for denitrification and aerobic respiration, as well as genes for central metabolic pathways, providing key precursors essential for ATP production and cellular biosynthesis. Our findings elucidate the role of the residual plant phyllosphere as a microbial hotspot of N2O emissions in agricultural fields. This is the study demonstrating denitrifiying bacteria present on leaves and their functions as drivers of N2O production. Furthermore, we demonstrate that denitrification, which is known as an anaerobic process, can occur by utilizing nutrients released from senescent leaves, even on the leaf surface surrounded by air. Our study expands the ecological niche of denitrification from belowground soil to aboveground plants in terrestrial ecosystems.